Artificial Bee Colony Algorithm for Solving Initial Value Problems - Djerou, L.; Khelil, N.; Aichouche, S. (Communications in Mathematics and Applications, 2017)
A novel numerical differential equation method is presented to solve approximately an initial-value problem (IVP). The IVP is formulated as an optimization problem and the artificial bee colony algorithm (ABC) is used in order to find numerical solutions for this problem. Finally, we use an initial value problem example as illustration to testify the efficiency of the proposed method. The computational results showed that the proposed new method is quite promising, and the potential of the algorithm could be applied successfully in near future to other numerical method as well.